Photoluminescent tetrahedral d(10)-metal Schiff base complexes exhibiting highly ordered mesomorphism - Chakraborty, Sutapa; Purkayastha, Debraj Dhar; Das, Gobinda; Bhattacharjee, Chira R.; Mondal, Paritosh; Prasad, S. Krishna; Rao, D. S. Shankar (Polyhedron, 2016)
A series of four-coordinate d(10)-metal complexes of the type [ML2] {M = Zn, Cd, Hg; L = 4-nitro-2-((octadecylimino)methyl)phenol}, incorporating a new N-alkylated bidentate [N,O]-donor salicylaldimine Schiff base ligand, has been synthesized and characterized by elemental analyses, FT-IR, UV-Vis, H-1 NMR and FAB-mass spectroscopies. The ligand is non-mesomorphic and devoid of any photoluminescence. The zinc(II) and cadmium(II) complexes displayed highly ordered mesophases reminiscent of soft crystals. The phases have been characterized by polarizing optical microscopy (POM), differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD) studies. The complex of mercury(II) decomposed prior to melting. An orthogonal symmetry with a `herringbone' array for the zinc complex and a primitive triclinic symmetry (p(1)) for the cadmium complex, respectively, has been proposed. The complexes exhibited fluorescence at room temperature, both in the solution and in the solid state, with emission maxima in the blue region. Density functional theory (DFT) calculations carried out using the GAUSSIAN 09 program at the B3LYP level revealed a distorted tetrahedral geometry around the metal center in all the complexes. Natural bond orbital (NBO) analysis suggested appreciable charge transfer from the ligand to the metal center in the complexes. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Density functional theory; Luminescence; Mesophase; Schiff base; X-ray diffraction